IMPLEMENTASI PENEGAKAN PERDA NO. 22 TAHUN 2013 TENTANG PENERTIBAN REKLAME OLEH SATUAN POLISI PAMONG PRAJA (SATPOL PP) KABUPATEN KEPULAUAN MENTAWAI - Bobby Sinukaban; Marwandizal Marwandizal; Daniel Jusari (Jurnal Public Administration, Business and Rural Develoment Planning, 2021)
The research objectives are: 1) To find out how to implement the enforcement of Perda No. 22 of 2013 concerning Control of Billboards by the SatPol PP of the Mentawai Islands Regency. 2) To find out what obstacles are faced. 3) To find out what efforts were made to overcome the obstacles faced.This research uses descriptive method, and based on the result of this study. 1) Implementation of enforcement of the Mentawai Islands District Regulation No. 22 of 2013 concerning Control of Advertisements by SatPol PP, among others: a) Data collection related to violations found in the Implementation of Advertisements, b) Submission of Data Offenders Then confirmed to the Mentawai Islands Regency Licensing Service, c) Execution. 2) The obstacles faced include: a) There are still people who do not understand the regulations contained in the Perda itself, b) There are still individuals who deliberately commit fraud that violate existing regulations, c) Limited equipment in executing banners / billboard. 3) Efforts made in overcoming the obstacles faced include: a) Carrying out guidance and outreach to the community and business actors regarding the regulations of the Mentawai Islands District Regulation No. 22 of 2013 concerning Control of Billboards, b) Carrying out routine patrols to directly execute violations of the implementation of billboards and information media as well as dismantling of valid permits, c) Procurement of equipment to execute billboards / billboards or megatrons.